A indústria cultural no mercado cinematográfico: Um Plot Twist pela Geografia - Jesus, Jhennifer Mariano de (Universidade Federal de São Carlos, 2025)
This monograph aims to develop a reflection on the culture industry based on the film market. In this sense, a theoretical basis was developed to understand important concepts in the area, highlighting the power of the culture industry in the context of geopolitics, from a geographical point of view, integrating these elements and seeking to understand this phenomenon. Thus, films that represented the culture industry in its molds were selected, the films nominated in the “Best Picture” category of the 2024 Oscar awards. After selection, the films were analyzed and divided into thematic categories, which indicate the main subjects addressed in the works, seeking to understand the role of cinema in today's world, which generates influence in international relations driven by globalization. Furthermore, at the end of the work, maps were created to help visualize the culture industry role in Brazil and the selected films influence in the Brazilian film market.
The cultural industry in the cinematographic market: A Plot Twist by geography
Keywords: Indústria Cultural; Cinema; Geopolítica; Globalização; Culture Industry; Geopolitics; Globalization; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA